The Effect Of Career Development, Organizational Culture On Job Satisfaction And Its Impact On Turnover Intention At Pt Xyz Bandung - Deanida Pratiwi, Intan; Poerwita Sary, Fetty (International Journal of Science, Technology & Management, 2023)
The purpose of this study aims to determine the effect of career development, organizational culture on Job Satisfaction and its Impact on Turnover Intention at PT XYZ Bandung. The analytical method used in this study is the Structural Equation Modeling (SEM) method using SmartPLS software. program. This research is included in quantitative research with data collection methods in the form of questionnairess and survey. The research held at PT XYZ Bandung with 140 sample people. The statistical test results all hypotesis are accepted. Based on the results it shows that the research model produces a positive t-statistics value and the t-table = df (n-k) is 1.656. It can be concluded that the greater the value of an exogenous variable on an endogenous variable, the stronger the effect. As for the indirect effect of the largest endogenous variable is on the variable Career development (5.045) and organizational culture (4.528). The significance level used in this study is 5%. Therefore, if the p-values ? 0.05 then the hypothesis is accepted while if the p-values> 0.05 then the hypothesis is rejected. Based on the table above, the results show that all hypotheses are accepted.